The Effect of Crude Protein Level in Diets on Laying Performance, Nutrient Digestibility of Yellow Quails - Li, Y.X.; Wang, Y.Q.; Pang, Y.Z.; Li, J.X.; Xie, X.H.; Guo, T.J.; Li, W.Q. (International Journal of Poultry Science, 2011)
Four diets with different crude protein levels 17.75%, 19.95%, 21.85%, 24.08% were used to feed 192 seven-week-old yellow quails in this experiment. During 50-day-old to 95-day-old, laying rate, feed intake and egg weight were recorded to analysis the effect of different levels of dietary protein on the performance of yellow quails. All fences were collected and analysis the effect of different levels of dietary protein on feed digestibility and Crude Protein utilizablity of yellow quails. The results showed that there was no significant difference of the average egg weight in four diets. The laying rate of diet 2 is significant high than others (p<0.05). The difference of the average feed intake was significant (p<0.05) and feed intake of the diet 1 was the highest. Feed intake/egg was significant (p<0.05). There was no significant difference of crude fiber digestibility (p>0.05) but significant of EE and total organism and the utilizability of crude protein was significant difference (p<0.05) in four diets. Result showed that dietary crude protein had significant effect not only on laying performance but also on nutrient digestibility and 20% dietary crude protein was optimum for yellow-feather quails.